2017
DOI: 10.1108/ajim-04-2017-0098
|View full text |Cite
|
Sign up to set email alerts
|

Gender and image sharing on Facebook, Twitter, Instagram, Snapchat and WhatsApp in the UK

Abstract: Mike Thelwall, Farida Vis Purpose: Despite the ongoing shift from text-based to image-based communication in the social web, supported by the affordances of smartphones, little is known about the new image sharing practices. Both gender and platform type seem likely to be important, but it is unclear how. Design/methodology/approach: This article surveys an age-balanced sample of UK Facebook, Twitter, Instagram, Snapchat and WhatsApp image sharers with a range of exploratory questions about platform use, priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 29 publications
3
46
1
4
Order By: Relevance
“…Although gender effects have been reported in previous studies [2,21,30] and we found a significant difference in usage levels with women interacting significantly more with Snapchat than men, gender does not appear to be a significant predictor for Snapchat use in our sample. In contrast to gender, age was consistently a significant predictor for Snapchat usage with a high beta weight.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Although gender effects have been reported in previous studies [2,21,30] and we found a significant difference in usage levels with women interacting significantly more with Snapchat than men, gender does not appear to be a significant predictor for Snapchat use in our sample. In contrast to gender, age was consistently a significant predictor for Snapchat usage with a high beta weight.…”
Section: Discussioncontrasting
confidence: 79%
“…Pew Research Center [20] reports for 2018, that in the US, 23% of men and 31% of women declared using Snapchat. Differences in usage have been also observed, with Thelwall and Vis [30] findings that men were more likely to share images on Twitter while women used Snapchat more with the same intent. This trend was the same for posting frequency.…”
Section: Introductionmentioning
confidence: 88%
“…It allows for information sharing, participatory and collaborative interactions among groups of users [126]. Social media has provided varieties of innovative interaction systems [127,128] and meets the need for instant access to information [129]. These media applications have been found by many studies [124,[130][131][132] as critical contemporary information tools.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, regulatory effectiveness is expected to be an antecedent of trust in institution in this study. Further, prior studies have provided increasing evidences that females and males differ in their decisions relevant to trust (Thelwall and Vis, 2017). Riedl et al (2010) also indicate that different trust building mechanisms may work in different ways for males and females.…”
mentioning
confidence: 99%